KEEFEKTIFAN PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK TEKS AURAL - Dinar Nursyifa; Iis Ristiani (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to determine the effectiveness of using audio-visual media in improving listening skills in aural texts among 10th grade students at SMK Ar-Rahmah, Cianjur. The method used was quantitative with a pre-experimental design and a one-group pretest-posttest pattern. The data collection techniques included tests, observations, and questionnaires. The data analysis process in this study used N-Gain calculations to determine the extent of improvement in listening skills. In addition, a t-test (paired sample t-test) was used. The results showed that the use of audio-visual media was effective, resulting in an improvement in students' listening skills. This was evident from the test results, which showed an increase with an n-gain value of 80.12%, which was classified as high. Student activity during learning also showed excellent engagement, with a 90% percentage. In addition, student responses to learning through questionnaires obtained an average score of 91%, which means that students responded very positively to the use of audio-visual media in learning.